Performance of Spleen Stiffness, Liver Stifness, and their Combination for Predicting Esophageal among Patient with HBV-Related Cirrhosis - Billy Stinggo Siahaan; Juferdy Kurniawan; Marcellus Simadibrata; Aulia Rizka; Andri Sanityoso; Cleopas Martin Rumende; Andhika Rachman; Hamzah Shatri (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Liver cirrhosis in Indonesia still become a burden disease, and the etiology is mostly from the hepatitis B virus. Esophageal varices (EV) is the most common complication of portal hypertension in liver cirrhosis. Due to many reasons, esophagogastroduodenoscopy is still not fully suitable for routine surveillance in daily practice. Hence, studies that work in the search for the best non-invasive test are still important for predicting EV.